Strigolactones constrain rice drought acclimation by suppressing ROS scavenging through the D53–OsWRKY31–ZFP36 module - Qianqian Li; Yi Wang; Jijun Yan; Liquan Kou; Hao Zhang; Jinhua Yang; Qingliang Hu; Yanshuo Guo; Xinwei Ban; Nan Luo; Peiyong Xin; Yanhui Jing; et al. (Molecular Plant, 2026)

Tracking Cretaceous to present day deep-sea sedimentary hiatuses driven by intensified bottom-water currents - Jiewei Hu; Dengfeng Li; David Chew; Simon W. Poulton; Yanhui Dong; Jinzhou Peng; Yu Fu; Xiaoming Sun (Earth and Planetary Science Letters, 2026)

Environmentally relevant doses of fluoride exposure mediate kidney injury by affecting Tregs/Teffs homeostasis - Bingshu Liu; Siqi Zhu; Dan Wei; Qiong Zhang; Guiyu Fu; Xiudian Li; Yanhui Gao; Wei Wei (Chemico-Biological Interactions, 2026)

Synthesis of N, S-co-doped carbon quantum dots derived from coralline algae polysaccharide and their application for grape preservation in gelatin films - Libo Wang; Xuan Fu; Kerou Gao; Yuhan Song; Hongda Zhang; Yanhui Wei; Kun Cheng (Food Bioscience, 2026)

Heavy metals at environmentally relevant concentrations enhance antibiotic and ammonia removal in constructed wetlands - Chengkai Fu; Jian Zhang; Donglin Wang; Zeyu Hao; Yanhui Zhao; Changqing Liu; Huaqing Liu; Huijun Xie; Haiming Wu; Zhen Hu (Journal of Hazardous Materials, 2026)

Performance of novel media-based aquaponics under stress of different antibiotics: Role of biochar and zero-valent iron - Muhammad Tanveer; Chengkai Fu; Linlan Zhuang; Yanhui Zhao; Doinglin Wang; Peihan Yu; Yiqiao Zhang; Zhen Hu (Journal of Hazardous Materials, 2026)

Comparative analysis of greenhouse gas emissions and energy consumption of composite cold-mixed asphalt mixture based on life cycle assessment - Bei Zhang; Xiaoka Yin; Yanhui Zhong; Quansheng Zang; Yu Fu; Shaowei Fu; Yaqi Li; Mingyang Ma (Journal of Cleaner Production, 2025)

A highly efficient tungsten carbide catalyst for natural Photothermal-Driven formic acid dehydration reaction - Maoyu Xu; Cuncai Lv; Deyi Zhang; Dongyang Zhao; Yanhui Fu; Yaguang Li; Jinhua Ye (Fuel, 2025)

Development and characterization of phosphate tailings-based humic acid slow-release fertilizer using ball milling sludge acid activation - Yinxin Xie; Qi Zhang; Deyi Yuan; Yingjie Hu; Caiyuan Guo; Muhammad Atif Muneer; Yafu Tang; Yanhui Xu; Fu Wan; Youzhi Yang (Process Safety and Environmental Protection, 2025)

Quantifying Impacts of Human Activities and Climate Change on Runoff Variation: A Case Study of Songhua River Basin, China - Wenhan Pei; Jiping Liu; Yanhui Chen; Guobin Fu; Chongya Ma; Yufei Liu (Chinese Geographical Science, 2025)

A ratiometric fluorescence sensor based on Eu3+ doped LDH@CMCh gel for visual detection and effective adsorption of tetracycline antibiotics - Xiaoli Guo; Jiaxiao Niu; Yixin Meng; Yongpeng Ma; Ruiyu Fu; Jiawei Liu; Xiaoqin Hai; Hongbo Li; Yanhui Zhang; Xin Di (Carbohydrate Polymers, 2025)

Design and Performance Study of a Six-Bar Mechanism Underwater Robot Based on Cownose Ray Bionics - Yichen Chu; Xiaohan Wang; Tiancheng Hao; Yanhui Fu; Yubing Duan; Tianbiao Yu (Journal of Marine Science and Engineering, 2025)
This paper focuses on the formidable challenges that underwater robots encounter in complex marine environments. To address these issues, inspired by the cownose ray, an innovative scheme is proposed, utilizing four six-bar mechanisms to mimic its pectoral fin movement. Subsequently, the paper elaborates on the design, computation, and simulation of the bionic pectoral fin mechanism. A Watt-type six-bar mechanism is adopted, and by axially overlaying two scaled-identical mechanisms and setting a phase difference, the pectoral fin waving of the cownose rays is simulated. SolidWorks and ADAMS are employed for precise modeling and simulation. Following this, an experimental prototype is constructed, with the rod assembly produced by subtractive machining. Motion capture and six-dimensional force experiments are then conducted to evaluate its motion dynamics and propulsion efficacy. The experimental results demonstrate that when the two pectoral fins on either side flap synchronously or inversely, the robot can generate varying thrust, lift, and lateral forces, enabling smooth advancement and turning. These findings validate the feasibility and efficacy of bionic design, offering innovative concepts and methodologies for underwater robot development.

Molecular composition difference of electron donating moieties between natural organic matter and effluent organic matter probed by chlorine dioxide - Quan Gao; Yanheng Pan; Yangjian Zhou; Jianglin Peng; Qingqing Kong; Yanhui Cheng; Qing-Long Fu; Xin Yang (Water Research, 2025)

Frabrication of carboxymethylchitin nanofibers and fish gelatin hybrid gels with robust gel performance - Rongqiang Chen; Shuai Zhang; Jiao Jiao Sun; Lijuan Xu; Yuan Duan; Fengchen Li; Yanhui Han; Xiao Fu; Meng Wang; Yong Hong Meng; Yurong Guo (Food Hydrocolloids, 2025)

Chemodiversity of coastal seawater dissolved organic matter shaped by wastewater treatment plant effluent in Tokyo Bay, Japan - Yanhui Cheng; Jibao Liu; Manabu Fujii; Qing-Long Fu (Applied Geochemistry, 2025)

Molecularly imprinted polymer gel with superior recognition and adsorption capacity for amphenicol antibiotics in food matrices - Ruiyu Fu; Xiaoqin Hai; Qingxin Lu; Hongbo Li; Jiaxiao Niu; Yanhui Zhang; Tingze Ren; Xiaoli Guo; Xin Di (Food Chemistry, 2025)

Evaluation of wind-induced response of high-rise structure with TMD system by real-time hybrid simulation test with motor-driven shaking table - JiaLei Wang; JiYang Fu; JiuRong Wu; YanHui Liu; HuiMeng Zhou; Ching Tai Ng; QiongXiang Liu (Engineering Structures, 2025)

Hollow mesoporous Prussian blue nanoenzymes as Rapamycin carrier for targeted treatment of ischemia/reperfusion-induced acute kidney injury through pro-mitophagy and oxidative stress alleviation - Yanhui Wang; Huayu Fu; Bangqi Huang; Ziyang Liang; Yijun Shen; Yulan Wang; Jun Wu; Yi Zhao (Chemical Engineering Journal, 2024)

Plasma-derived exosomal miRNA profiles reveal potential epigenetic pathogenesis of premature ovarian failure - Jiaqiong Lin; Zhihong Wu; Yingchun Zheng; Zongrui Shen; Zhongzhi Gan; Shunfei Ma; Yanhui Liu; Fu Xiong (Human Genetics, 2024)

Rare earth element enrichment process of bioapatite in deep-sea REY-rich sediments - Hao Wang; Zhenggang Li; Yanhui Dong; Bin Fu; Xiaohu Li; Jie Li; Fengyou Chu; Weiyan Zhang; Zhiming Zhu; Jihao Zhu; Ling Chen (Chemical Geology, 2024)

PKC-θ is an important driver of fluoride-induced immune imbalance of regulatory T cells/effector T cells - Siqi Zhu; Bingshu Liu; Guiyu Fu; Liu Yang; Dan Wei; Liwei Zhang; Qiong Zhang; Yanhui Gao; Dianjun Sun; Wei Wei (Science of The Total Environment, 2024)

Switchable deep eutectic solvent as green and efficient media for liquid-phase microextraction of phenoxyacetic acid herbicides in water and food matrices - Jiaxiao Niu; Yanhui Zhang; Hongbo Li; Xiaoqin Hai; Qingxin Lu; Ruiyu Fu; Tingze Ren; Xiaoli Guo; Xin Di (Food Chemistry, 2024)

Effects of Chemical Fixatives on Kinetic Measurements of Biomolecular Interaction on Cell Membrane - Tianbao Dong; Shengyang Wan; Yanhui Wang; Yaru Fu; Pengcheng Wang (The Journal of Membrane Biology, 2024)

Study on the lateral thermal disturbances of three parallel embankments on permafrost along the Gonghe-Yushu Engineering Corridor in China - Binhua Hu; Long Jin; Yanhui Niu; Zhipeng Fu; Xu Li; Yuanhong Dong; Kun Yuan; Ziqiao Zhao (Transportation Geotechnics, 2024)

Sulfur isotopic systematics of hydrothermal precipitates in the Okinawa Trough: Implication for the effect of sediments and magmatic volatiles - Hao Wang; Zhenggang Li; Bin Fu; Jie Li; Fengyou Chu; Yanhui Dong; Jihao Zhu; Zhimin Zhu; Ling Chen; Xiaohu Li (Chemical Geology, 2024)

Structural analysis of shield machine cutting monopile using p-y curve based finite element method - Ting Li; Bo Liu; Yanhui Han; Chunqing Fu; Yanding Sun (Computers and Geotechnics, 2023)

Transcription factor ELK1 regulates the expression of histone 3 lysine 9 to affect developmental potential of porcine preimplantation embryos - Yuanshen Zhao; Yanhui Zhai; Cong Fu; Lijing Shi; Xiangjie Kong; Qi Li; Hao Yu; Xinglan An; Sheng Zhang; Ziyi Li (Theriogenology, 2023)

Cenozoic basement-involved rifting of the northern South China Sea margin - Yanhui Suo; Sanzhong Li; Guangrong Peng; Xiaodong Du; Jie Zhou; Pengcheng Wang; Guangzeng Wang; Ian Somerville; Yixiao Diao; Zhongqiang Liu; Xinjian Fu; Bo Liu; et al. (Gondwana Research, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Changes of nitrogen and phosphorus removal pattern caused by alternating aerobic/anoxia from the perspective of microbial characteristics - Kai Yao; Xiao Huang; Wenyi Dong; Fupeng Wang; Xueyong Liu; Yu Yan; Yanhui Qu; Yicheng Fu (Environmental Science and Pollution Research, 2023)

Seed nanopriming: How do nanomaterials improve seed tolerance to salinity and drought? - Mohammad Nauman Khan; Chengcheng Fu; Jiaqi Li; Yunpeng Tao; Yanhui Li; Jin Hu; Lingling Chen; Zaid Khan; Honghong Wu; Zhaohu Li (Chemosphere, 2023)

Factors Affecting Differential Methylation of DNA Promoters in Arsenic-Exposed Populations - Yanting Zhang; Yuanyuan Li; Lanrong Luo; Qian He; Yanhui Gao; Hongqi Feng; Lijun Zhao; Wei Wei; Songbo Fu; Dianjun Sun (Biological Trace Element Research, 2019)

Greening China Naturally - Shixiong Cao; Ge Sun; Zhiqiang Zhang; Liding Chen; Qi Feng; Bojie Fu; Steve McNulty; David Shankman; Jianwu Tang; Yanhui Wang; Xiaohua Wei (Ambio, 2011)